Bioassay guide isolation of antibacterial compounds from Andrographis paniculata - Sule, Abubakar; Ahmed, Qamar Uddin; Abd. Samah, Othman; Omar, Muhammad Nor; Mohd Hassan, Norazian; Mohd Kamal, Laina Zarisa; Yarmo, Mohd Ambar (Science Publications, 2011)
Problem statement: Chronic disease-causing bacteria of medical importance have developed resistance to antibiotics, hence, necessitating distinct and constant need for safe and efficient therapeutic agents. Plants are considered potent candidate for this aim. A way out of reducing antibiotic resistance and adverse effects on host is the employment of antibiotic resistance inhibitors of plant origin.